2004
DOI: 10.1089/152091504773731285
|View full text |Cite
|
Sign up to set email alerts
|

Alarms Based on Real-Time Sensor Glucose Values Alert Patients to Hypo- and Hyperglycemia: The Guardian Continuous Monitoring System

Abstract: The purposes of this study were to demonstrate the accuracy and effectiveness of the Guardian Continuous Monitoring System (Medtronic MiniMed, Northridge, California) and to demonstrate that the application of real-time alarms to continuous monitoring alerts users to hypo and hyperglycemia and reduces excursions in people with diabetes. A total of 71 subjects with type 1 diabetes, mean hemoglobin A1c of 7.6 +/- 1.1%, age 44.0 +/- 11.4 years, and duration of diabetes 23.6 +/- 10.6 years were enrolled in this tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 14 publications
1
117
1
5
Order By: Relevance
“…Table 1 summarises characteristics of the included trials. Five RCTs involving 131 participants met our predefined inclusion criteria [15][16][17][18][19]; the remaining 20 studies were excluded [7,[11][12][13][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Table 2 summarises the characteristics of excluded trials, including reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarises characteristics of the included trials. Five RCTs involving 131 participants met our predefined inclusion criteria [15][16][17][18][19]; the remaining 20 studies were excluded [7,[11][12][13][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Table 2 summarises the characteristics of excluded trials, including reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…One trial [17] showed an Bode et al [20] Non-randomised, uncontrolled trial Bode et al [7] RCT performed in adults. Guardian Continuous Monitoring System used Boland et al [21] Non-randomised, uncontrolled trial Burdick et al [22] Non-randomised, uncontrolled trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while better measurements are always beneficial, measurement error itself does not appear to have a greater impact than the TGC protocol design or its ability to manage inter-and intra-patient variability. [142][143][144][145]). For TGC in the ICU this area was also reviewed in [66].…”
Section: The Impact Of Measurement Frequency and Error And Implicatimentioning
confidence: 99%
“…These CGMS devices incorporate real-time alarms when the measurement exceeds the safe range threshold. 1,2 Using general guidelines that patients follow in their daily life, some diabetes management systems have been proposed to further assist patients in self-managing their disease, such as CareLink personal software (Medtronic, Northridge, CA), which is a secure, Web-based therapy management software that allows patients to easily store their information and allows a healthcare professional access to it. 3 One of the most essential components of a diabetes management system is the BG prediction scheme.…”
Section: Introductionmentioning
confidence: 99%